Establishing and characterizing organoid cultures from colon tissue of South African individuals - Du Plessis, Thea-Leonie (University of the Witwatersrand, Johannesburg, 2024)
Colorectal cancer (CRC) has been poorly studied in South Africa, with limited studies on disease progression and development. Studies that have investigated CRC in South Africa have indicated that there is racial disparity between different racial groups that may be attributed to alternative developmental pathways, differences in genetic compositions or CRC initiators that result in these different clinical presentations. Furthermore, the lack of population-based studies substantiates the need for more intensive CRC research. A particular model used to study cancer in general is the use of two-dimensional (2D) cell cultures, which have provided novel insight into many cancers and their development processes. However, these models lack the complex biology observed in vivo. One such model that is gaining research interest is the use of three-dimensional (3D) organoid cultures. Organoids are derived from stem cells and are able to self-organize and mimic the corresponding organ from which they were derived. Research has indicated that organoids are able to maintain cell-type heterogeneity as well as gene expression levels that resemble the organ of origin. Therefore, this project aimed at standardizing a protocol to establish and characterise colorectal organoid cultures from South African patient-derived tissues. Patient samples were obtained from individual patients with informed consent and were processed to generate organoids. The morphology of the organoids was monitored across several days and across passages. Once the organoids had reached maturity and were at passage 2, characterization was performed using real-time quantitative polymerase chain reaction (RT-qPCR) and immunofluorescence which indicated that the genetic composition and spatial localization of cell types of interest in non-cancerous tissue was recapitulated in the organoids. Based on these observations, it is proposed that organoids could be a promising model to investigate CRC disease development and progression and potentially search for novel therapeutics. This project has established the protocols for growing and characterizing organoids from African samples and provides baseline data, and outlines the complexities and issues involved in growing organoid cultures for the future studies
A Dissertation Submitted in fulfillment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Colorectal cancer; Organoids; Estamblishment; Characterization; UCTD; SDG-3: Good health and well-being